2020
DOI: 10.1136/tsaco-2020-000593
|View full text |Cite
|
Sign up to set email alerts
|

Dilemma of crystalloid resuscitation in non-exsanguinating polytrauma: what is too much?

Abstract: BackgroundAggressive crystalloid resuscitation increases morbidity and mortality in exsanguinating patients. Polytrauma patients with severe tissue injury and subsequent inflammatory response without major blood loss also need resuscitation. This study investigated crystalloid and blood product resuscitation in non-exsanguinating polytrauma patients and studied possible adverse outcomes.MethodsA 6.5-year prospective cohort study included consecutive trauma patients admitted to a Level 1 Trauma Center intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…1. Ninety-one percent of injuries (n = 213) were caused by a blunt mechanism and median Injury Severity Score (ISS) was 33 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) with most severe injuries located in the brain (AIS head 3 (0-4)) and chest (AIS chest 3 (2-4)). Physiology, resuscitation, and outcome data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Ninety-one percent of injuries (n = 213) were caused by a blunt mechanism and median Injury Severity Score (ISS) was 33 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) with most severe injuries located in the brain (AIS head 3 (0-4)) and chest (AIS chest 3 (2-4)). Physiology, resuscitation, and outcome data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This is confirmed by the fact that crystalloids < 24 h were an independent predictor for mortality. Additionally, we have demonstrated in a previous study that large amounts of crystalloids are known to attribute to increased mortality [ 32 ]. Crystalloid administration < 24 h does not fully explain the differences in AUC between surviving and deceased patients since AUC was measured until base deficit normalization or up to 48 h, and BD was again within normal limits < 48 h in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Prospective data have suggested increased mortality in patients who receive more than 15 L of crystalloids within 24 hours of hospital presentation. 3 An even larger prospective review suggested that administration of more than 1.5 L of fluid is correlated with increased mortality. 4 A review of 1754 patients from the Glue Grant Database suggested that larger volumes of crystalloid administered within the first 24 hours after injury were correlated with more ventilator days, longer intensive care unit (ICU) and hospital length of stay, and higher rates of acute respiratory distress syndrome (ARDS), multi-organ failure, compartment syndromes, and infectious complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases it may be more useful to administer plasma instead, to prevent acute respiratory distress syndrome or multiple organ dysfunction syndrome. 15 18) In addition, hemodynamic monitoring (e.g., stroke volume and pulse pressure variations) is recommended to evaluate the reactivity of fluid management. 11) …”
mentioning
confidence: 99%